A Rare Case of Chromoblastomycosis Resembling Keloid in an Indonesian Child - Khairani, Fatima A; Pamela, Ruri D (Curēus (Palo Alto, CA), 2021)
Chromoblastomycosis (CBM) is a rare chronic fungal infection caused by various dematiaceous fungi. This mycosis is mostly found in middle-aged males in tropical and subtropical countries. Only few cases of CBM in children have been reported. The diagnosis of CBM is often delayed due to the similarities with other dermatological diseases, such as cutaneous tuberculosis, mycetoma, leprosy, viral warts, psoriasis vulgaris, or malignancies. We report a case of an 11-year-old healthy boy having CBM. On his left knee, there were large erythematous plaques and tumors with scaly surfaces, some lesions appeared to be cauliflower-like. The patient denied pain and pruritus. The preliminary diagnosis was keloid; however, histopathological findings led to the final diagnosis, which was established as CBM. The patient was treated with oral itraconazole 100 mg daily. His lesions partially resolved within one month of treatment. Although uncommon in children, the differential diagnosis of CBM must be considered in any suspicious lesion(s). Itraconazole 100 mg daily gave a good response in children with CBM. Accurate diagnosis and early treatment are needed to achieve successful management of CBM in children.